2017
DOI: 10.1186/s12886-017-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the natural course of visual acuity and quality of life in neovascular age-related macular degeneration: a systematic review and quality of life study

Abstract: BackgroundDescribing the natural course of neovascular age-related macular degeneration (nAMD) is essential in discussing prognosis and treatment options with patients and to support cost-effectiveness studies.MethodsFirst, we performed a literature search in PubMed, Embase, and Cochrane. We included randomized clinical trials and prospective observational studies reporting visual acuity (VA) in non-treated patients, 24 studies in total. We integrated VA data using best fit on Lineweaver-Burke plots and modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…; Elshout et al. ). Therefore, we believe that the time horizon of the CEA ideally should be 4 years (with little to no extrapolation of disease progression needed) or more (with proper extrapolation).…”
Section: Methodsmentioning
confidence: 98%
“…; Elshout et al. ). Therefore, we believe that the time horizon of the CEA ideally should be 4 years (with little to no extrapolation of disease progression needed) or more (with proper extrapolation).…”
Section: Methodsmentioning
confidence: 98%
“…For example, a recent study of a large US real-life cohort revealed stable mean VA with +/− 0 letters at one year 12 . This is considerably better than the natural history of untreated nAMD but far from the VA gains found in randomized clinical trials (RCTs) 13 . The main difference between real-life data and RCTs is that RCTs represent a highly selected cohort of patients.…”
Section: Discussionmentioning
confidence: 83%
“…In comparing PDT and anti-VEGF, we needed to adjust for CNV lesion type, since PDT was not indicated for all lesions, and we observed a difference in lesion types between PDT and anti-VEGF groups (Table 1). Furthermore, lesion type determines the prognosis [37][38][39]. We found that, after adjusting for lesion type, occult or classic CNV, there was no effect of PDT.…”
Section: Addressing Confoundingmentioning
confidence: 99%